1998
DOI: 10.1302/0301-620x.80b6.8176
|View full text |Cite
|
Sign up to set email alerts
|

Wear of congruent meniscal bearings in unicompartmental knee arthroplasty

Abstract: Many designs of unicompartmental knee replacement show early and mid-term failure due to polyethylene wear. We studied the wear rate of congruent polyethylene meniscal bearings retrieved from failed Oxford unicompartmental knee replacements. We examined 16 bearings, 0.8 to 12.8 years after implantation, measuring their thickness and comparing it with that of 14 unused bearings. The mean rate of penetration, which included the effects of wear at both upper and lower surfaces, was 0.036 mm per year (maximum 0.08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(37 citation statements)
references
References 6 publications
2
35
0
Order By: Relevance
“…We noted that the patients in whom failure occurred were younger than the group as a whole which gave rise to the suggestion that a mobile device could have helped in the more active young group since these have been shown to have a very low rate of polyethylene wear. 28,29 The recently reported ten-year survivorship of the mobile-bearing Oxford device is 91% 30 in patients under 60 years old, which is comparable with the 11-year survivorship of 92% reported for a fixed-bearing device in a similar young group of patients. 31 The challenge remains to treat this younger group of active patients successfully and reproducibly, but for more elderly patients with unicompartmental disease, our results support the use of a fixed-bearing cemented device.…”
Section: Discussionsupporting
confidence: 58%
“…We noted that the patients in whom failure occurred were younger than the group as a whole which gave rise to the suggestion that a mobile device could have helped in the more active young group since these have been shown to have a very low rate of polyethylene wear. 28,29 The recently reported ten-year survivorship of the mobile-bearing Oxford device is 91% 30 in patients under 60 years old, which is comparable with the 11-year survivorship of 92% reported for a fixed-bearing device in a similar young group of patients. 31 The challenge remains to treat this younger group of active patients successfully and reproducibly, but for more elderly patients with unicompartmental disease, our results support the use of a fixed-bearing cemented device.…”
Section: Discussionsupporting
confidence: 58%
“…Psychoyios et al [38] state that revision surgery is not always a solution, as in one of every four revisions the problem is not solved. This series suggests that patients with complaints of pain should be investigated, carefully followed up, and revision for unexplained pain must be avoided as it may not be warranted in these cases [23].…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for its rising popularity are the introduction of minimally invasive surgical (MIS) techniques [31, 41] with modified surgical equipment, the publication of the excellent medium- and long-term results of the Oxford Phase 2 arthroplasty [14, 39, 44, 45] and the well-documented improved polyethylene wear characteristics of the mobile bearing device [18, 38]. Medial osteoarthritis of the knee is considered to be a unicompartmental disease and, when left untreated, it may later progress to involve the other knee compartments [1].…”
Section: Introductionmentioning
confidence: 99%
“…Revision arthroplasty does not cure pain in every case, and in SKAR 2004 [34] unexplained pain following UKRs was reported to be 5–6 %. Such procedures are often not only unnecessary but also ineffective [23]. In our study, four patients (2.28 %) were revised to TKR at an average of 31.7 months (range 19–54 months) for persistent pain.…”
Section: Discussionmentioning
confidence: 81%
“…Polyethylene wear has often been cited as a cause of failure after UKR, more so in association with flat articulating surfaces than with congruent mobile bearings [19, 2123]. Berger et al [24] reported no revisions for polyethylene wear in a series of 51 knees that were treated with flat articulating surface (fixed-bearing Miller−Galante).…”
Section: Discussionmentioning
confidence: 99%